Implementasi Model Pembelajaran Betuah Untuk Meningkatkan Aktivitas Belajar, Pemecahan Masalah Dan Hasil Belajar Siswa Pada Muatan Matematika Di Kelas III Mi Al-Aman - M. Miftah Asshadiqy; Herti Prastitasari (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem in this research is that learning activity is still low, lack of problem solving abilities and low learning outcomes. These problems are caused by students not being involved enough in learning, minimal application of learning models, students not understanding the same lesson because there are no group activities, evaluation questions not yet HOTS oriented and low learning outcomes. Therefore, efforts that can be made to improve learning activities, problem solving abilities and learning outcomes are through the BETUAH model. The aim of this research is to describe teacher activities, analyze student activities in the learning process, analyze problem solving abilities and analyze improvements in learning outcomes. This research used Classroom Action Research (PTK) which was carried out in 4 meetings. The subjects of this research were class III MI AL-AMAN students, totaling 21 students, in the second semester of the 2023/2024 academic year. The data analysis technique in this research is quantitative data obtained through written test techniques and qualitative data obtained through observation sheets. The results of this research show that teacher activity at meeting I only reached a score of 24, at meeting 4 it increased to 32, then student activity increased, which at meeting I only reached 57%, at meeting IV it increased to 100%. Problem solving ability at meeting I reached 15% at meeting IV increased to 100%. Classical completeness of learning outcomes at meeting I only reached 43% and increased at meeting IV to 100%. Based on the results of this research, it can be concluded that the use of the BETUAH model can be implemented and students can follow the learning process accordingly, thereby increasing learning activities, problem solving abilities and learning outcomes. The suggestion for school principals, teachers and other researchers is that this research can be used as a reference in using learning models that can improve learning activities, problem solving abilities and learning outcomes.